Suicide Attempt with Rodenticide Including Zinc Phosphide Case Report - Yıldız, İsa and Akgül, Sibel and Özkan, Süreyya and Güneş, Hacı Yusuf and Bayır, Hakan and Özdeş, Taşkın (The Bulletin of Legal Medicine, 2015)
Zinc phosphide is a toxic chemical agent used as a rodenticide. The effects are on heart, lung, kidney and gastrointestinal tract. Metabolic acidosis, high amylase, liver damage, hypotension, shock and cardiac arrhythmia is observed. Forty-year-old male patient evaluated with a history of taking zinc phosphide containing rat poison in order to commit suicide. Respiratory distress, arrhythmias, commonly involuntary muscle contraction, metabolic acidosis, coagulation disorders, amylase, AST and LDH levels were determined. Term follow-up after intensive care unit and was discharged favor. In this paper, for the purpose of suicide zinc phosphide our experiences in the field of public information in the cases of ICU follow-up treatment process is intended to share the accompaniment.